A holistic methodology for designing novel flat plate evacuated solar thermal collectors: Modelling and experimental assessment - Barone, Giovanni; Buonomano, Annamaria; Kalogirou, Soteris A.; Ktistis, Panayiotis K.; Palombo, Adolfo (My University, 2024)
This paper presents a comprehensive analysis of the design, implementation, experimentation, and optimization of a novel evacuated flat-plate solar thermal collector characterized by a vacuum level between the glass cover and the absorber plate. The paper addresses different research themes, primarily focusing on developing a low-cost evacuated solar thermal collector with a high innovation level. Additionally, it introduces a comprehensive approach for the conceptualization, design, fabrication, testing, and optimization of solar thermal collectors. Specifically, this study aims to highlight the characteristics of a vacuum-enhanced solar thermal collector and demonstrate a step-by-step process involved in its design, fabrication, testing, and optimization. The proposed methodology is based on the adoption of two software tools and an extensive experimental analysis: the commercial software ANSYS is utilized for structural analysis, while MatLab is employed to develop a suitable mathematical tool for assessing the energy performance of the system and optimizing it. The outcomes show the reliability of the methodology and the performance of the low-cost evacuated solar thermal collector under different vacuum levels, providing insights into energy, economic, and environmental aspects. This work innovates by presenting a thorough analysis covering all solar thermal collector production phases, from conceptualization to optimization. The conclusions highlight the production of a reliable approach, and proof-of-concept results demonstrate how increasing the vacuum level enhances the thermal efficiency of a solar collector.
Keywords: Vacuum solar thermal collector; Solar energy; Modelling; Energy performance analysis